Courage To Be Superior - Patterson, Grove (Tufts Archival Research Center, 2006)
Grove Patterson describes his belief in a Supreme Power who created the universe, in immortality, in the efficacy of prayer, in the existence of natural law, in the existence of evil caused by humans, and in the courage to face rather than withdraw from the world's problems.